Assessment of Kitchen Waste Generated in a Maternity Hospital: A Case Study in Brazil - Moura, Leonardo de Lima; Mahler, Claudio Fernando; Caulliraux, Heitor Mansur (Ciência e Natura, 2017)
Healthcare waste management (HCWM) is at problem in many developing countries. One of the main steps to implement a proper HCWM process is knowledge of the amount and composition of material generated. There are rare studies of the contribution of kitchen waste to the total mass of non-hazardous waste generated by hospitals in the world. This paper reports a diagnosis of waste generation by the kitchen of a maternity hospital in the state of Rio de Janeiro, Brazil. Using the method established by the World Health Organization (WHO), non-hazardous wastes of all sectors were weighed for seven consecutive days in July and August, 2015. The average kitchen waste generated was 92.77 kg.day-1 and 76,73 kg.day-1, respectively, corresponding to 43.65% and 46.44% of the total mass of general waste produced in the period, although there was no positive correlation between the generated mass of kitchen waste and the number of meals prepared and served. We concluded that kitchen waste poses a considerable challenge to HCWM, mainly involving temporary internal storage, external storage and container cleaning, as well in the physical conditions of the workers that transport the waste.